Analysis of Competency Development at PT Unilever Indonesia Tbk from 2020 to 2023 - Pidha Tri Rahayu (Nomico, 2024)
This study analyzes the competency development at PT Unilever Indonesia Tbk during the period from 2020 to 2023. The data used are sourced from the company's Sustainability Report. The analysis covers the competency development programs provided, the number of employees participating, and the impact of training on employee performance. The results indicate that Unilever consistently increased its investment in human resources (HR) for competency programs, with a focus on developing technical and leadership skills, and continually evolving competency development patterns with the introduction of new training programs.